Radiation-Induced Hyalinizing Clear Cell Carcinoma of the Orbit. Issue 1 (January 2021) - Topping, Katie L.; Ortiz, Angelica; Lin, Jonathan H.; Kossler, Andrea L.
Abstract : Radiation-induced malignancy is rare, occurring in approximately 0.4%–1.0% of patients receiving external beam radiation therapy. Sarcomas and squamous cell carcinomas are among the most common types of cancers to occur. A 74-year-old woman presented with redness and swelling in the right periorbital region. She had history of multiple recurrent ameloblastoma of the right maxilla, invading the right orbital floor status post 4 surgical resections and 66 Gray external beam radiotherapy 5 years prior. MRI showed a poorly circumscribed mass involving the inferior and lateral orbit. Orbital biopsy revealed clear cell carcinoma with hyalinizing sclerosis and Ewing sarcoma breakpoint region 1 gene arrangement. Due to the extent of orbital disease and presence of perineural invasion, she underwent orbital exenteration. Hyalinizing clear cell carcinoma, a rare cancer, has not been reported to occur in the orbit following radiation. This case highlights the importance of lifetime monitoring in patients who have undergone radiation therapy. Abstract : Hyalinizing clear cell carcinoma of the orbit is a rare, usually low-grade malignancy that may develop following radiation treatment and exhibit high-grade features such as perineural invasion.